Elevated pretransplant pulmonary vascular resistance index does not predict mortality after isolated orthotopic heart transplantation in children: A retrospective analysis of the UNOS database. (15th July 2015) - Chiu, Peter; Schaffer, Justin M.; Sheikh, Ahmad Y.; Ha, Richard; Reinhartz, Olaf; Mainwaring, Richard; Reitz, Bruce A.
Abstract OHT is the definitive therapy in end‐stage heart failure. Elevated PVRI is considered a relative contraindication to isolated OHT; this assumption is re‐evaluated using data from the UNOS database. A retrospective review of de‐identified data from the UNOS dataset was performed. There were 1943 pediatric OHT recipients between 10/87 and 12/11 with sufficient data for analysis. Cox regression was performed to examine the effect of baseline characteristics on post‐transplant survival. Patients were propensity matched, and Kaplan–Meier survival analysis was performed comparing cohorts of patients using thresholds of 6 and 9 WU × m2. PVRI was not a significant predictor of post‐transplant outcomes in either univariate or multivariate Cox regression. Kaplan–Meier analysis revealed no difference in survival between both unmatched and propensity‐matched OHT recipients. In conclusion, elevated PVRI was not associated with post‐transplant mortality in pediatric OHT recipients. A prospective study assessing the current use of PVRI ≥6 as a threshold to contraindicate isolated OHT should be undertaken. Removing this potentially unnecessary restriction on transplant candidacy may make this life‐saving therapy available to a greater number of patients.